Placement of network services in a sensor network. (19th February 2007) - Yick, Jennifer; Pasternack, Gregory; Mukherjee, Biswanath; Ghosal, Dipak
An important challenge in designing a wireless sensor network is to maximise the network's lifetime. In a hierarchical cluster-based network, a key design issue is the placement of cluster heads (data loggers) such that the total power consumed by the overall network is minimised. Another key design goal is the localisation of sensors. In this study, we consider the placement of beacons and data loggers in the Cosumnes River Preserve. We consider a hybrid network in which the wireless sensors are deployed randomly into an irregular terrain while the data loggers and beacons are placed in a planned manner to satisfy the following three objectives: provide complete area coverage; load balance each cluster; minimise the total power consumption for collecting the data. We formulated an optimisation problem to determine the location of data loggers and beacons – which is solved using an Integer Linear Program (ILP).